Analisis Strategi Pemasaran Dalam Upaya Meningkatkan Penjualan UKM Es Permen Karet 2320 Di Kabupaten Lamongan - Wisnu Priambodo; Danu Kusbandono; Elvyna Dhamayanti (CV. Multi Kreasi Media, 2022)
Ice Chewing Gum 2320 is one of the SMEs that produces beverages. The purpose of this study is to analyze the competitive advantage of the Ice Gum 2320 competitive strategy which is located on Jalan Sumargo (PKL Lamongan Lamongan Complex No. 1C). This study uses qualitative data in the form of primary and secondary data. The data collection technique was carried out through interviews and direct observation to the Ice Gum Chewing SMEs. This research uses SWOT, STP, and 4P analysis methods. The results of the swot analysis show that the Strength strategy is a strategic location and a lower price than competitors. Weaknesses strategy is the location with the rental status and the lack of production equipment such as ice cooling machines. The Opportunities strategy is to increase the number of visitors and the high level of purchasing power of the Lamongan population. Threats strategy is the growth of new competitors and similar competitors with lower prices. Segmenting results are carried out based on demographic and psychographic aspects. Targeting results are companies focusing on all groups, especially teenagers. Positioning results are the company's position as a beverage company that provides ready-to-drink beverages in Lamongan district.